Preparation of Three Types of Transformer Oil-Based Nanofluids and Comparative Study on the Effect of Nanoparticle Concentrations on Insulating Property of Transformer Oil - Qi Wang; Muhammad Rafiq; Yuzhen Lv; Chengrong Li; Kai Yi (Journal of Nanotechnology)
Nanofluids have the potential to become the alternatives of conventional transformer oil for their exquisite electrical and thermal properties. Three kinds of nanoparticles with distinct conductivities, namely, nonconductive nanoparticle Al2O3, conductive nanoparticle Fe3O4, and semiconductive nanoparticle TiO2, with different concentrations from 5% to 40% w/v were selected and suspended into transformer oil to develop nanofluids. The lightening impulse breakdown strengths of the oil samples with and without nanoparticles were measured according to IEC standard methods. The positive impulse breakdown strength indicated that breakdown strength is first increased up to the maximum value at certain concentration and then starts decreasing. The results of negative impulse breakdown manifested that the breakdown voltages of nanofluids with different concentrations were less than the breakdown voltage of pure transformer oil. Different effect mechanisms of dielectric and conductive nanoparticles were also used to describe the difference among three prepared nanofluids.